Pengaruh Resiliensi, Gaya Kepemimpinan, Komunikasi, dan Motivasi Terhadap Kepuasan Kerja Karyawan - Reza Yogi Adi Pratama; Yudhistira Pradhipta Aryoko; Hengky Widhiandono; Ika Yustina Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study This study aims to test and analyze the effect of resilience, leadership style, communication, and work motivation on employee job satisfaction. leadership, communication, and work motivation on employee job satisfaction at An Ni'mah General Hospital Wangon, Banyumas Regency. at An Ni'mah General Hospital Wangon, Banyumas Regency. This type of research is quantitative-survey research. The population in this study were employees of An Ni'mah Wangon Hospital, Banyumas Regency, totaling 280 employees. totaling 280 employees. The sample was taken using the Roscoe formula which amounted to 105 employees at An Ni'mah Wangon General Hospital, Banyumas Regency. Technique sampling technique in this study using Simple Random Sampling (SRS) technique. The research instrument used a questionnaire. Analysis techniques in this study This study uses Smart Partial Least Square (Smart-PLS) 3.0 statistical analysis. used for validity test, reliability test and hypothesis testing. Results This study proves that leadership style and work motivation affect employee job satisfaction at An Ni'mah General Hospital. while resilience and communication have no effect on job satisfaction of An Ni'mah General Hospital employees of An Ni'mah General Hospital.